2013
DOI: 10.14413/herj.2013.01.05.
|View full text |Cite
|
Sign up to set email alerts
|

Youth, Religion, Socialization. Changes in youth religiosity and its relationship to denominational education in Hungary

Abstract: The aim of this paper is to explore the main characteristics of religious change among the Hungarian youth and to assess the impact of the denominational schools compared to that of the religious upbringing in the family on their religiosity. Previous empirical studies have found a considerable level of unchurching in Hungary affecting first and foremost the membership of the highly institutionalized traditional churches. Recent scholarly literature emphasizes the significance of age explaining secularization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
2
0
3
Order By: Relevance
“…The findings of research projects conducted among Hungarian youth reflect that out of civic organizations, it is the churches, i.e., religious associations, that attract young people the most (Csako, 2004;Szabo, Bauer, & Laki, 2002). In the course of the Magyar Ifjusag 2016 research, half the students reported that they belonged to some denomination, 25% of them had received a religious upbrining, and 20% of them had learned what they knew about faith in some religious organizations (Hamori & Rosta, 2013). The results of the series of the surveys we conducted in the geographical region mentioned above suggest that an average of 20% of the students belonged to some religious youth organizations (Pusztai, 2015).…”
Section: Membership In a Religious Community And Persistencementioning
confidence: 89%
“…The findings of research projects conducted among Hungarian youth reflect that out of civic organizations, it is the churches, i.e., religious associations, that attract young people the most (Csako, 2004;Szabo, Bauer, & Laki, 2002). In the course of the Magyar Ifjusag 2016 research, half the students reported that they belonged to some denomination, 25% of them had received a religious upbrining, and 20% of them had learned what they knew about faith in some religious organizations (Hamori & Rosta, 2013). The results of the series of the surveys we conducted in the geographical region mentioned above suggest that an average of 20% of the students belonged to some religious youth organizations (Pusztai, 2015).…”
Section: Membership In a Religious Community And Persistencementioning
confidence: 89%
“…Az azóta eltelt két évtized alatt a vallásos nevelésben részesültek, a magukat az egyház tanítása szerint vallásosnak vallók, valamint a rendszeresen templomba járók aránya csökkent a fiatalok körében (Bauer et al 2016), s az egyházi iskolahálózatok bővülésével több, nem vallásos hátterű tanuló is bekerülhetett ezekbe az intézményekbe, vizsgálandó, hogy milyen hatást gyakorol a felekezeti iskola a különböző vallásosságú családokból érkezőkre. Többen vizsgálták a vallási szocializáció hatékonyságát, a családi és iskolai vallásos nevelés hatását (Hámori-Rosta 2013;Kisnémet 2015b;Pusztai 2020). A felekezeti iskolák diákjait a kortársakkal összehasonlító hazai elemzések a felekezeti iskola önálló hatását mutatták ki, mindenekelőtt a "maga módján" vallásosságra, amenynyiben az elsődleges szocializáció vallásos jellegének hatását kiszűrtük (Hámori-Rosta 2013;Pusztai 2020).…”
Section: Az Egyházi Iskola Mint a Vallási Szocializáció áGenseunclassified
“…Többen vizsgálták a vallási szocializáció hatékonyságát, a családi és iskolai vallásos nevelés hatását (Hámori-Rosta 2013;Kisnémet 2015b;Pusztai 2020). A felekezeti iskolák diákjait a kortársakkal összehasonlító hazai elemzések a felekezeti iskola önálló hatását mutatták ki, mindenekelőtt a "maga módján" vallásosságra, amenynyiben az elsődleges szocializáció vallásos jellegének hatását kiszűrtük (Hámori-Rosta 2013;Pusztai 2020). Az értékrend tekintetében szintén szignifikáns, de a teljes felnőtt lakosság tekintetében tapasztalhatónál (Földvári 2004) kisebb mértékű különbség volt ki mutatható a vallásosak és nem vallásosak (Rosta 2002), illetve az felekezeti iskolát választók és nem választók között (Pusztai 2020).…”
Section: Az Egyházi Iskola Mint a Vallási Szocializáció áGenseunclassified
See 1 more Smart Citation
“…Previously the one-way linear reconstruction models determined the approach of studying religious socialization in Hungarian research on religiosity (Pusztai 2006;Kiss 2007;Hámori and Rosta 2013). The reason for this is that the institutional forms of religious education were limited in the decades of communism in the Central European region.…”
Section: Introductionmentioning
confidence: 99%